EKSPLORASI DAN KARAKTERISASI MORFOLOGI TANAMAN KOPI ROBUSTA (COFFEA CANEPHORA) DI KAWASAN GUNUNG KARANG - Siahaan, Gita Shania Seprionika; Yenny, Ratna Fitry; Ritawati, Sri; Hermita, Nuniek (Fakultas Pertanian Universitas Mataram, 2024)
Genetic diversity of Robusta coffee plants (Coffea canephora) can be known by identifying morphological characters. Local Robusta coffee is found in the Karang Mountain area. This study aims to determine the diversity of morphological characters and characteristics that distinguish between plant samples in the Karang Mountain area. This research is an exploratory and descriptive survey with a purposive sampling technique. The variables observed were vegetative and generative morphological characters of plants. The results showed that there was a diversity of plant morphological characters and there were characteristics that distinguished between Robusta coffee plant samples in the Gunung Karang area. Vegetative characters include plant stature, plant height, plant shape, stem stature, stem branching shape, stipule shape, young leaf color, leaf shape, leaf tip shape, leaf edge shape, leaf length, and leaf width. Generative characters include fruit color, fruit shape, fruit width, fruit thickness, seed width, seed thickness, seed color, and seed shape.